Cognitive Analysis of Village Potential Basic Integration in BUMDEs Managers in North Aceh District, Lhokseumawe City and Bireun District - Likdanawati, Likdanawati; Hamdiah, Hamdiah; Sutriani, Sutriani; Ilham, Rico Nur; Multazam, Muhammad (Malikussaleh University, Aceh, Indonesia, 2025)
Currently, the government continues to strive to build and develop the rural economy through community empowerment programs to increase productivity, business diversity, and regional potential, as well as improve the economy and welfare of rural communities. One of the government's programs is to provide a budget for funds in the field of community empowerment, which will be used to support the capital for establishing Village-Owned Enterprises (BUMDEs). This follows the objectives of BUMDEs, namely optimising the management of village assets and existing village potentials to support the village economy and improve the welfare of rural communities. But unfortunately, until now, the role and function of BUMDEs have not been effective or felt by the community. This is due to the inability and lack of professionalism of BUMDEs' management human resources, and the lack of integration of businesses managed by BUMDEs with existing village potentials, so that it seems as if BUMDEs stands only as a formality without supporting the economic potential of the village community. This study aims to create a strategic concept in BUMDEs management so that it runs more effectively and on target to support the village economy through the development of human resource knowledge in BUMDEs management, integrated with the economic potential of the village community. So, BUMDEs and Basic Pontesial village are integrated into a business institution that supports the village economy for the welfare of the village community. This solution can help village communities strengthen their economy and provide a view of knowledge and open insights to BUMDEs managers so that they can develop BUMDEs into a business that synergises with the community. This study uses primary data from questionnaires and interviews aimed at BUMDEs management employees to see the extent of their abilities, expertise, and knowledge to evaluate and innovate in the business. In analysing the data, this study uses the Maslahah Scorecard measurement method, which refers explicitly to performance measurements oriented towards the welfare of the people (society). The output of this study is the publication of a reputable national journal and a reference book of research results certified by an ISBN with an initial TKT level of TKT 1. A Final TKT Target of TKT 3, namely this study, will focus on the Integration of Basic Village Potential in BUMDEs Managers in North Aceh Regency, Lhokseumawe City and Bireun Regency.